SIMULATION OF QUEUE PATIENT SERVICE - Cipta, Hendra (UIN Sumatera Utara Medan, 2017)
Queue is one of the phenomena that occur in everyday activities experienced by everyone. As a result of this queue many people turn to other places to avoid a queue and get more leverage. The purpose of this study is to study the performance of the queue system by modeling a single queue simulation. From the analysis of distribution test calculation will be obtained by queuing model. The measured system parameters are expected average speed velocity, average service speed expectation, chance of busy period, probability of all patient service in system, expectation of queue length, expectation of waiting time in system, and waiting expectation in queue.Keywords: distribution test, queuing model, and system parameters